Mainstreaming revisited: Experiences from eight countries on the role of National Biodiversity Strategies in practice - Cardona Santos, E.; Kinniburgh, F.; Schmid, S.; Büttner, N.; Pröbstl, F.; Liswanti, N.; Komarudin, H.; Borasino, E.; Ntawuhiganayo, E.; Zinngrebe, Y. (Elsevier, 2023)
Global biodiversity targets have not been met due to weak implementation at the national level. National Biodiversity Strategies and Action Plans (NBSAPs) are central for mainstreaming biodiversity by translating global ambition into national policies. This study analyzes the practical role of global and national biodiversity agendas. Interviews from France, Germany, Honduras, Indonesia, Mexico, Peru, Rwanda, and South Africa show that global targets and NBSAPs have raised awareness, mobilized initiatives, mobilized support for implementation, and fostered accountability. Nevertheless, conflicting interests, weak financial support, and poorly integrated institutional and regulatory structures remain challenges to implementation. Levers for harnessing the role of future NBSAPs to achieve the goals and targets of the Kunming-Montreal Global Biodiversity Framework are: improving communication; defining concrete measures and clear responsibilities; fostering cross-sectoral commitment; enshrining targets into national laws; ensuring adequate public funding; reforming harmful subsidies; ensuring coordination among sectors and levels of governance; and strengthening accountability frameworks.